2016
DOI: 10.1016/j.exger.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Gene-nutrient interaction markedly influences yeast chronological lifespan

Abstract: Purpose Research into the genetic mechanisms of aging has expanded rapidly over the past two decades. This has in part been the result of the use of model organisms (particularly yeast, worms and flies) and high-throughput technologies, combined with a growing interest in aging research. Despite this progress, widespread consensus regarding the pathways that are fundamental to the modulation of cellular aging and lifespan for all organisms has been limited due to discrepancies between different studies. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 55 publications
(98 reference statements)
3
41
0
Order By: Relevance
“…Here we showed that msc6 and ifm1 mutants present low viability in two different longevity/survival assays in agreement with some recent data but distinct from others mitochondrial translational factors mutants . At any rate, the best method to measure yeast life span is controversial and depends on several factors, moreover different genome‐wide screens life span studies present little overlap, probably as a consequence of genetic background and experimental conditions .…”
Section: Discussionsupporting
confidence: 89%
“…Here we showed that msc6 and ifm1 mutants present low viability in two different longevity/survival assays in agreement with some recent data but distinct from others mitochondrial translational factors mutants . At any rate, the best method to measure yeast life span is controversial and depends on several factors, moreover different genome‐wide screens life span studies present little overlap, probably as a consequence of genetic background and experimental conditions .…”
Section: Discussionsupporting
confidence: 89%
“…Chronological lifespan, in contrast, is defined as the length of time that an individual yeast cell can maintain viability in a non-dividing quiescent state and yet retain the ability to re-enter the cell cycle upon appropriate stimulation (Fabrizio and Longo, 2003). Studies of both types of aging in yeast have uncovered novel mechanisms of aging (Kaeberlein, 2010; Longo and Fabrizio, 2012; Mirisola et al, 2014), and genome-wide analyses have been carried out for both replicative (McCormick et al, 2015; Smith et al, 2008b) and chronological (Burtner et al, 2011; Fabrizio et al, 2010; Matecic et al, 2010; Powers et al, 2006; Smith et al, 2016) lifespan, which have identified multiple genetic modifiers of aging in yeast that are shared with multicellular eukaryotes (discussed further below).…”
Section: Dietary Restriction In S Cerevisiaementioning
confidence: 99%
“…Genetic analysis of the CLS of budding yeast has led to the genome-wide identification of genes involved in aging; recent efforts have sought to describe interactions between genetic and environmental modulators of the phenotype 13,[15][16][17] . A previous report from our group has shown some advantages of using a competitive-aging approach, in which fluorescently-labeled strains in co-culture provide high resolution in parallel setups 13 .…”
Section: Discussionmentioning
confidence: 99%
“…While this may be explained in part by differences in genotypic background, media composition, and subtle environmental variations 17 , the large fraction of false positives and little overlap may also suggest that available large-scale CLS phenotyping approaches are still lacking enough technical replicability. Moreover, changes in specific controlled and uncontrolled environmental conditions are known to be important modifiers of CLS phenotypes and may be confounding causes of aging 12,[17][18][19][20] . Hence, a combination of high throughput and good resolution is needed to correctly determine not only genetic aging factors, but also to quantitatively derive their interactions with nutrimental, chemical, or pharmacological environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation